Analisis Pilihan Moda Transportasi Umum Rute Padang â Jakarta Menggunakan Metode Stated Preference (Analysis of Public Transportation Mode Choice for Padang-Jakarta Route using Stated Preference Method) - Fidel Miro (The Institute for Research and Community Services, Institut Teknologi Bandung, 2016)
Abstract. Padang-Jakarta is one of the traffic routes in Indonesia on a national scale that can be categorized as busy. Every day people involved in diverse activities travel between both cities. Current conditions indicate that the people traveling between the two cities are served by 2 modes of transportation, i.e. public inter-city/inter-province (AKAP) bus services and domestic airlines operating daily. In his study, the favored transportation modes used to travel between both cities were analyzed by applying stated preference and discrete choice modeling to find the service attributes and variables that have the most significant influence on the traveler's satisfaction when using both alternative transportation modes. After analyzing the data collected from a total of 100 randomly selected persons with the stated preference approach, one of the results obtained was: Umode i = 1.723 + 2,618T - 0,004C + 7,180VT, which means that value of time (VT) affected traveler satisfaction significantly more than attributes such as total travel time (T) and total cost of the trip (C). Therefore, the probability of air transportation to be used for traveling the route Padang-Jakarta is larger (52%) than that of the alternative transportation mode (AKAP public bus). This means that the providers of both modes of transportation, airlines and AKAP public bus services, should focus their attention on timeliness of departure, departure frequency and delay minimization while maintaining the other attributes of their service, such as affordable tariffs, fleet condition, as well as others. Keywords. Transportation Mode Choice, Public Transportation, Padang-Jakarta Route, Stated Preference Method.